Non-contiguous finished genome sequence and description of Bartonella saheliensis sp. nov. from the blood of Gerbilliscus gambianus from Senegal. (May 2020) - Dahmana, H.; Medkour, H.; Anani, H.; Granjon, L.; Diatta, G.; Fenollar, F.; Mediannikov, O.
Abstract: Bartonella saheliensis strain 077 (= CSUR B644T; = DSM 28003T) is a new bacterial species isolated from blood of the rodent Gerbilliscus gambianus captured in the Sine-Saloum region of Senegal. In this work we describe the characteristics of this microorganism, as well as the complete sequence of the genome and its annotation. Its genome has 2 327 299 bp (G+C content 38.4%) and codes for 2015 proteins and 53 RNA genes.